Teenage mutant ninja turtles (2011), volume 13 ebook Vengeance, part 2. - Eastman, Kevin (Teenage Mutant Ninja Turtles (2011), 2015)
The Turtles take the fight to Baxter Stockman, while Karai decrees a "Gauntlet" battle between ancient foes Splinter and Shredder all leading to a final showdown that will determine the fate of NYC, and the world, for years to come! Collects issues #48–50. Author: Kevin Eastman, Tom Waltz. Illustrator: Mateus Santolouco, Cory Smith. © 2018 Viacom International Inc. All rights reserved. TEENAGE MUTANT NINJA TURTLES and all related titles, logos, and characters are trademarks of Viacom International Inc. Based on characters created by Peter Laird and Kevin Eastman.